Tingkat Pengetahuan Kecacingan Di Desa Sukasari Pandeglang - David Tjahyadi; Edy Parwanto; Haryo Ganeca Widyatama; Sisca Sisca; Reza Aditya Digambiro; Alfred Pakpahan (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Worm disease still a serious problem and is second health problem in Indonesia come after malnutrition. Cumulative worms in human body can cause loss of substances that are useful for growth. The Filariasis and Worm Worms Sub-Directorate of P2PL stated that the prevalence of worm diseases in Pandeglang Regency was 58.3%. Various worm larvae were found when examining soil samples taken at the homes of residents of Sukasari, Pulosari, Pandeglang villages. The aim of this community service (PKM) is to increase knowledge about worm diseases. This Community Service Method (PKM) uses the counseling or lecture method by the presenter. Before and after counseling, residents were given a questionnaire to measure their level of knowledge about worm diseases. Residents' knowledge increased after being given counseling and it is hoped that this can help the community to prevent the emergence of worm diseases in the future.